2021
DOI: 10.3390/ma14216464
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of 3D Printing Parameters on Adhesion between Polylactic Acid (PLA) and Thermoplastic Polyurethane (TPU)

Abstract: A 3D printer in FDM technology allows printing with two nozzles, which creates an opportunity to produce multi-material elements. Printing from two materials requires special consideration of the interface zone generated between their geometrical boundaries. This article aims to present the possibility of printing with PLA and TPU using commercially available filaments and software to obtain the best possible bond strength between two different polymers with respect to printing parameters, surface pattern (due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 41 publications
2
26
0
1
Order By: Relevance
“…Fused Deposition Modeling (FDM) technology is just one from many technologies which are covered with Additive Manufacturing (AM) process. It is possible to produce components from metallic materials, from resins and also from polymers [1][2][3]. Fused Deposition Modeling is the most wide-spread technology.…”
Section: Introductionmentioning
confidence: 99%
“…Fused Deposition Modeling (FDM) technology is just one from many technologies which are covered with Additive Manufacturing (AM) process. It is possible to produce components from metallic materials, from resins and also from polymers [1][2][3]. Fused Deposition Modeling is the most wide-spread technology.…”
Section: Introductionmentioning
confidence: 99%
“…One such study reports the use of epoxy-based resins for laminated object manufacturing of polymeric material to explore the adhesive strength of epoxy resins in the case of polymers [ 19 ]. Brancewicz et al [ 20 ] reported on the adhesive strength of the epoxy resins for the PLA and TPU composites [ 20 ]. The reported studies on polymeric composites using epoxy resins have evaluated and observed the adhesive strength of the material by testing the single lap joint by using the typical ASTM D1002 testing standard [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reported studies on polymeric composites using epoxy resins have evaluated and observed the adhesive strength of the material by testing the single lap joint by using the typical ASTM D1002 testing standard [ 21 ]. It has been ascertained that the epoxy resins have adhesive strength in between the range of 10–15 MPa for a range of materials [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The challenge of FDM direct-printed multi-material parts is their adhesion. Several researchers investigated the printing parameters on adhesion and properties of multi-material 3D printing for the multi-material structure made with a combination of PLA and TPU [ 13 , 17 , 18 ]. Brancewicz-Steinmetz et al found that proper printing parameters and TPU on PLA print sequences result in better adhesion between materials [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers investigated the printing parameters on adhesion and properties of multi-material 3D printing for the multi-material structure made with a combination of PLA and TPU [ 13 , 17 , 18 ]. Brancewicz-Steinmetz et al found that proper printing parameters and TPU on PLA print sequences result in better adhesion between materials [ 17 ]. Kepenekci and Zhang proposed implementation of a mechanical lock mechanism and bio-inspired arrangement of the structure to improve the adhesion between the printed PLA/TPU interface, respectively [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%